Antibacterial cobalt-based composite coating for aluminum alloy surface as well as preparation method and application of antibacterial cobalt-based composite coating
By using laser cladding technology to form an antibacterial cobalt-based composite coating on the surface of aluminum alloy, the problems of insufficient coating thickness, low bond strength, and limited improvement in wear and corrosion resistance in the prior art are solved, and the high coating is achieved The binding force, multiple hardness improvement, corrosion resistance improvement by 2 orders of magnitude and significant antibacterial effect.
Patent Information
- Application Number
- CN202411624597.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
The existing aluminum alloy surface treatment methods have problems such as insufficient coating thickness, low bonding strength, and limited improvement in wear and corrosion resistance. They are especially vulnerable to erosion, corrosion and bacterial pollution in the marine environment, resulting in economic losses and shortened service life. .
Laser cladding technology is used to form an antibacterial cobalt-based composite coating on the surface of aluminum alloy, including the 309S metallurgical bonding transition layer and the CoCrWCu cladding layer. By strictly controlling the element content of Cu, the antibacterial, corrosion resistance and mechanical properties of the coating are improved.
It significantly improves the bonding force between the coating and aluminum alloy, enhances the hardness and corrosion resistance of the coating, significantly improves the antibacterial effect, and extends the service life of aluminum alloy.
Smart Images

Figure CN119433533A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of marine equipment protection, and specifically relates to an antibacterial cobalt-based composite coating for an aluminum alloy surface, and a preparation method and application thereof. Background Art
[0002] Aluminum alloy has the advantages of light weight, high plasticity, and machinability, and has important application value in industries such as shipbuilding, petrochemicals, automobiles, transportation, and aerospace. In the natural environment, a dense passivation film will be generated on the surface of aluminum alloy, thereby improving its corrosion resistance. However, due to its insufficient hardness and wear resistance, its application scope is seriously restricted, and it will cause great economic losses after damage. Improving its surface hardness and wear resistance is the key to expanding its application scope and extending its service life. The surface passivation film of aluminum alloy serving in the marine environment will become loose and porous, and is usually susceptible to harsh environmental factors such as high chloride ion concentration and high humidity, resulting in pitting, intergranular corrosion, and stress corrosion cracking (SCC), which seriously shortens the service life of aluminum alloy. Therefore, it is urgent to prepare a wear-resistant coating on its surface to solve this problem.
[0003] Existing aluminum alloy surface treatment methods (including anodizing, plasma spraying, thermal spraying, cold spraying, supersonic flame spraying, electroplating and plasma electrolytic oxidation, etc.) have shortcomings such as insufficient coating thickness, low bonding strength, and limited improvement in wear and corrosion resistance. With the rapid development of laser technology, the power and service life of lasers have been greatly improved in recent years, and the use of laser cladding technology to prepare high-performance coatings has also become a research hotspot in the coating field. However, there are currently no reports on the use of laser cladding technology to apply cobalt-based alloy coatings on aluminum alloy surfaces. This is because the high reflectivity of aluminum alloys to lasers and the extremely high thermal conductivity and thermal expansion coefficient of aluminum alloys make it impossible for cobalt-based coatings to form effective metallurgical bonds on aluminum substrates (see Figure 8 ).
[0004] In marine fluid power systems, erosion-corrosion and bacterial contamination are two key factors for metal components, resulting in huge losses to the global economy. Since both failures are surface-related, surface coatings with good mechanical properties, corrosion resistance, and antibacterial properties are urgently needed to protect alloy substrates from failure in harsh marine environments. Summary of the invention
[0005] The main purpose of the present invention is to provide an antibacterial cobalt-based composite coating for aluminum alloy surface and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: An embodiment of the present invention provides an antibacterial cobalt-based composite coating for an aluminum alloy surface, comprising: a 309S metallurgical bonding transition layer and a CoCrWCu cladding layer sequentially formed on the surface of an aluminum alloy substrate; wherein the 309S metallurgical bonding transition layer comprises the following element components: C, Ni, Mn, Si, C and Fe; the CoCrWCu cladding layer comprises the following element components: Cr, W, Cu, Mo, Fe, Si, Mn, C and Co; the Cu content in the CoCrWCu cladding layer is 2-4wt%; the antibacterial cobalt-based composite coating is prepared by laser cladding technology.
[0007] In the composition design of the antibacterial cobalt-based composite coating for aluminum alloy surface of the present invention, the element content of Cu needs to be strictly controlled. When the mass ratio of Cu is greater than 2wt%, the material can have excellent antibacterial function. However, considering the corrosion resistance and mechanical properties, the coating performance of 2% Cu is the best, so it is recommended that the copper content is 2wt%≤Cu ≤4wt%.
[0008] The embodiment of the present invention also provides a method for preparing the aforementioned antibacterial cobalt-based composite coating for the surface of aluminum alloy, which comprises: Providing an aluminum alloy substrate; Laser cladding technology is used to clad 309S powder material on the surface of aluminum alloy substrate to form a 309S metallurgical bonding transition layer; Furthermore, a high-speed laser cladding technology is used to clad the CoCrWCu powder material on the surface of the 309S metallurgical bonding transition layer, thereby preparing an antibacterial cobalt-based composite coating for the surface of the aluminum alloy.
[0009] The embodiment of the present invention also provides the application of the aforementioned antibacterial cobalt-based composite coating for the surface of aluminum alloy in the field of marine equipment protection.
[0010] Compared with the prior art, the present invention has the following beneficial effects: (1) The antibacterial cobalt-based composite coating of the present invention adopts a 309S metallurgical bonding transition layer, which improves the bonding strength between the coating and the aluminum alloy, so that the coating has better bonding strength during use, and the coating is not easy to peel off when encountering friction; (2) Compared with aluminum alloy, the hardness of the antibacterial cobalt-based composite coating in the present invention is significantly increased by several times; (3) Compared with aluminum alloy, the corrosion resistance of the antibacterial cobalt-based composite coating in the present invention in deep-sea environment is improved by 2 orders of magnitude; (4) The present invention introduces Cu into the CoCrWCu cladding layer in the antibacterial cobalt-based composite coating, thereby greatly improving the antibacterial effect of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0012] Figure 1 is a cross-sectional SEM image of the antibacterial cobalt-based composite coating prepared in Example 1 of the present invention; Figure 2 is the XRD composition diagram of the antibacterial cobalt-based composite coating prepared in Example 1 of the present invention; Figure 3 is a cross-sectional hardness diagram of the antibacterial cobalt-based composite coating prepared in Example 1 of the present invention; Figure 4 It is an electrochemical test-polarization curve diagram of the 309S transition layer, cladding layer and 7075 aluminum alloy on the surface of aluminum alloy 7075 prepared in Example 1 of the present invention; Figure 5 It is a graph showing the sterilization results of the coatings with different Cu contents prepared in Example 1, Example 2, Example 3, Comparative Example 3 and Comparative Example 4 of the present invention in an Escherichia coli bacterial liquid environment; Figure 6 It is a graph showing the sterilization results of coatings with different Cu contents prepared in Example 1, Example 2, Example 3, Comparative Example 3 and Comparative Example 4 of the present invention in a Staphylococcus aureus bacterial liquid environment; Figure 7 It is a graph of the antibacterial rate of coatings with different Cu contents prepared in Example 1, Example 2, Example 3, Comparative Example 3 and Comparative Example 4 of the present invention against different bacteria; Figure 8 This is a macroscopic picture of the cladding layer directly laser clad on the aluminum alloy without using a transition layer in Comparative Example 1 of the present invention; Fig. 9 This is a cross-sectional SEM image of a coating in which no 309S transition layer is used and Fe60 is used as a transition layer for cladding in Comparative Example 2 of the present invention; Fig.10 It is a macroscopic picture of the composite coating surface in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0013] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0014] Specifically, as one aspect of the technical solution of the present invention, an antibacterial cobalt-based composite coating for an aluminum alloy surface comprises: a 309S metallurgical bonding transition layer and a CoCrWCu cladding layer sequentially formed on the surface of an aluminum alloy substrate; wherein the 309S metallurgical bonding transition layer comprises the following elemental components: C, Ni, Mn, Si, C and Fe; the CoCrWCu cladding layer comprises the following elemental components: Cr, W, Cu, Mo, Fe, Si, Mn, C and Co; the Cu content in the CoCrWCu cladding layer is 2~4wt%; the antibacterial cobalt-based composite coating is prepared by laser cladding technology.
[0015] In some preferred embodiments, the 309S metallurgical bonding transition layer includes the following element components calculated by mass percentage: Cr 22-24%, Ni 12-15%, Mn ≤2%, Si ≤1%, C ≤0.08%, and the rest includes Fe and unavoidable impurities.
[0016] In some preferred embodiments, the CoCrWCu cladding layer includes the following element components calculated by mass percentage: Cr 26~32%, W 3~6%, Cu 2~4%, Mo ≤1%, Fe ≤3%, Si ≤2%, Mn ≤1%, C ≤0.9~1.4%, and the rest includes Co element and unavoidable impurities.
[0017] In some preferred embodiments, the structure of the 309S metallurgical bonding transition layer is a single austenite phase.
[0018] In some preferred embodiments, the thickness of the 309S metallurgical bonding transition layer is 500-1000 μm.
[0019] In some preferred embodiments, the thickness of the CoCrWCu cladding layer is 700-1500 μm.
[0020] In some preferred embodiments, the structure of the CoCrWCu cladding layer is a single austenite phase.
[0021] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned antibacterial cobalt-based composite coating for the surface of an aluminum alloy, which comprises: Providing an aluminum alloy substrate; Laser cladding technology is used to clad 309S powder material on the surface of aluminum alloy substrate to form a 309S metallurgical bonding transition layer; Furthermore, a high-speed laser cladding technology is used to clad the CoCrWCu powder material on the surface of the 309S metallurgical bonding transition layer, thereby preparing an antibacterial cobalt-based composite coating for the surface of the aluminum alloy.
[0022] In some preferred embodiments, the 309S powder material includes the following element components calculated by mass percentage: Cr 22-24%, Ni 12-15%, Mn ≤2%, Si ≤1%, C ≤0.08%, and the rest includes Fe and unavoidable impurities.
[0023] In some preferred embodiments, the CoCrWCu powder material includes the following element components calculated by mass percentage: Cr 26~32%, W 3~6%, Cu 2~4%, Mo ≤1%, Fe ≤3%, Si ≤2%, Mn ≤1%, C ≤0.9~1.4%, and the rest includes Co element and unavoidable impurities.
[0024] In some preferred embodiments, the 309S powder material is in the form of spherical powder with a particle size of 15 to 53 μm.
[0025] In some preferred embodiments, the CoCrWCu powder material is in the form of spherical powder with a particle size of 15 to 53 μm.
[0026] In some preferred embodiments, the preparation method specifically includes: using laser cladding technology to clad 309S powder material on the surface of an aluminum alloy substrate to obtain a 309S metallurgical bonding transition layer; wherein the flow rate of the powder feeding gas used in the laser cladding technology is 12~20L / min, the laser power is 500~800W, the moving speed of the laser heat source is 18~22mm / s, the powder feeding amount is 6~8g / min, the single-channel lateral movement is 0.8~1.0mm, the distance between the laser head and the aluminum alloy substrate is 17~19mm, and the powder feeding gas includes argon and / or helium.
[0027] In some preferred embodiments, the preparation method specifically includes: using laser cladding technology to clad CoCrWCu powder material on the surface of the 309S metallurgical bonding transition layer to obtain a CoCrWCu cladding layer; wherein the flow rate of the powder feeding gas used in the laser cladding technology is 14~16L / min, the laser power is 400~600W, the moving speed of the laser heat source is 8~12mm / s, the powder feeding amount is 6~8g / min, the single-channel lateral displacement is 0.9~1.2mm, and the distance between the laser head and the 309S metallurgical bonding transition layer is 17~19mm; the powder feeding gas includes argon and / or helium.
[0028] In some preferred embodiments, the preparation method further comprises: first grinding the aluminum alloy substrate to remove the oxide scale, and then performing a cleaning treatment; wherein the cleaning treatment comprises: using ethanol or acetone to clean the surface of the aluminum alloy substrate obtained by the grinding treatment, at least to remove grease; And, the cleaned aluminum alloy substrate is placed on a heating table and preheated to 250-350° C. and kept heated continuously.
[0029] In some preferred embodiments, the preparation method further comprises: firstly drying the 309S powder material and the CoCrWCu powder material.
[0030] In some preferred embodiments, the aluminum alloy substrate comprises an aluminum alloy plate, and the thickness of the aluminum alloy plate is above 10 mm.
[0031] In some more specific embodiments, the method for preparing the antibacterial cobalt-based composite coating for the surface of aluminum alloy comprises: Providing an aluminum alloy substrate; Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale and then cleaned; wherein the cleaning treatment includes: using ethanol or acetone to clean the surface of the aluminum alloy substrate obtained by the polishing treatment, at least to remove grease; Place the cleaned aluminum alloy substrate on a heating table and preheat it to 250~350℃ and keep heating continuously; Laser cladding technology is used to clad 309S powder material on the surface of an aluminum alloy substrate to obtain a transition layer; wherein the flow rate of the powder feeding gas used in the laser cladding technology is 12-20 L / min, the laser power is 500-800 W, the laser heat source moving speed is 18-22 mm / s, the powder feeding amount is 6-8 g / min, the single-channel lateral movement is 0.8-1.0 mm, and the distance between the laser head and the aluminum alloy substrate is 17-19 mm; the powder feeding gas is argon or helium.
[0032] The CoCrWCu powder material is clad on the surface of the 309S transition layer by laser cladding technology to obtain an antibacterial cobalt-based composite coating; wherein the flow rate of the powder feeding gas used in the laser cladding technology is 14-16L / min, the laser power is 400-600W, the laser heat source moving speed is 8-12mm / s, the powder feeding amount is 6-8g / min, the single-channel lateral displacement is 0.9-1.2mm, and the distance between the laser head and the transition layer is 17-19mm; the powder feeding gas is argon or helium.
[0033] Another aspect of the embodiments of the present invention further provides the use of the aforementioned antibacterial cobalt-based composite coating for aluminum alloy surface in the field of marine equipment protection.
[0034] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0035] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0036] Example 1 (1) Powder treatment: 309S powder includes the following components calculated by mass percentage: Cr: 23%; Ni: 14%; Mn ≤ 2%; Si ≤ 1%; C ≤ 0.08%, and the rest is Fe element and other inevitable impurities; the particle size is 15-53μm.
[0037] The CoCrWCu powder includes the following components calculated by mass percentage: Cr: 28%; W: 4%; Cu: 2%; Mo≤1%; Fe≤3%; Si≤2%; Mn≤1%; C≤0.9%; the rest are Co element and other inevitable impurities; the particle size is 15-53μm.
[0038] The powder was dried in an oven before cladding.
[0039] (2) Substrate pretreatment: 7075 aluminum alloy is selected as the substrate material. Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale, and the surface of the aluminum alloy substrate obtained by the polishing treatment is cleaned with ethanol and acetone to at least remove grease. After cleaning, the aluminum alloy substrate is placed on a heating table and preheated to 300°C and kept heated continuously; (3) Preparation of transition layer: Argon gas was selected as the cladding protection gas and the cladding powder carrier gas. The 309S powder was clad on the surface of the aluminum alloy substrate by laser cladding technology to obtain the transition layer; the powder feeding gas flow rate was 15L / min, the laser power was 600W, the laser heat source moving speed was 20mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 0.9mm, and the distance between the laser head and the aluminum alloy substrate was 18mm; (4) Preparation of cladding layer Argon was selected as the cladding protection gas and the cladding powder carrier gas. The CoCrWCu powder was clad on the surface of the 309S transition layer by laser cladding technology to obtain a cladding layer (denoted as: CoCrW-2Cu), thereby preparing an antibacterial cobalt-based composite coating; the flow rate of the powder feeding gas was 15L / min, the laser power was 400W, the laser heat source moving speed was 10mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 1mm, and the distance between the laser head and the aluminum alloy substrate was 18mm.
[0040] (5) Structure and composition test: Test results: The transition layer and the substrate, the cladding layer and the transition layer show good metallurgical bonding. The cross-sectional SEM image is shown in Figure 2. Figure 1 As shown, the coating is dense and uniform, without defects such as pores and cracks. Figure 2 As shown, the antibacterial cobalt-based composite coatings are all austenite phase.
[0041] (6) Hardness test: Use Vickers hardness tester (Buehler Wilson VH3300) to measure the Vickers hardness of the cross section. Apply a load of 3N, keep the load for 10s and then unload. Each sample is tested at 8 points and the average value is taken. Test results: The average hardness of the substrate, 309S transition layer, and cladding layer is as follows: Figure 3 Compared with the aluminum substrate, the hardness of the coating is doubled.
[0042] (7) Corrosion resistance test: The electrochemical corrosion resistance test of the aluminum substrate and the prepared coating was carried out using an electrochemical workstation. The electrolyte used in the test was 3.5wt.% NaCl solution and the test temperature was room temperature. The test results are shown in the figure. Figure 4 As shown in FIG. 1 , it is a Tafel curve diagram of the electrochemical corrosion performance test of 7075 aluminum substrate, 309S transition layer and cladding layer. It can be seen that compared with aluminum alloy and transition layer, the coating has better corrosion resistance.
[0043] (8) Antibacterial performance test: The antibacterial performance of the antibacterial cobalt-based composite coating of this embodiment was tested in accordance with the standard GB / T 21866-2008 "Antibacterial coating (paint film) antibacterial property determination method and antibacterial effect", specifically: 0.4 mL of the test bacterial solution was added to the control sample (304 stainless steel) and the antibacterial cobalt-based coating sample. A homogenous film was covered with tweezers to ensure that the bacterial solution was spread flat and evenly distributed. After being placed in a culture dish, it was placed in a constant temperature incubator at 37°C and 90% humidity for 24 h. A 10 ml pipette was used to take 10 ml of SCDLP solution to rinse the sample surface and the bacterial solution on the homogenous film, and then 100 μL of the washed bacterial solution was taken and diluted with 900 μL of PBS solution. Then 100 μL of the diluted bacterial solution was dropped onto the agar plate, glass beads were added and shaken to make it evenly distributed, and then the beads were poured out to complete the coating (the same bacterial solution was coated three times to reduce experimental errors). All coated agar plates were inverted and placed in a constant temperature incubator at 37°C and 90% humidity for 24 h to allow the bacteria to grow. The number of colonies on the agar plates was counted and recorded using an automatic cell counter (interscience Scan 300). The mean of the three groups of parallel samples was calculated as the final number of colonies. The number of colonies on the agar plates with samples was compared with that of the control group, and the antibacterial cobalt-based composite coating was used to calculate the coating sterilization rate for bacteria (Escherichia coli, Staphylococcus aureus, etc.) according to the following formula: Sterilization rate (%) = (number of live bacteria in the control sample - number of live bacteria in the antibacterial cobalt-based coating) / number of live bacteria in the control sample × 100% Test results: The antibacterial effect of the control sample 304 stainless steel and the antibacterial cobalt-based composite coating is as follows Figure 5 (Escherichia coli E, concentration is 6×10 6 CFU / ml.) Figure 6 (Staphylococcus aureus S, concentration 6×10 6 CFU / ml), the antibacterial rate is shown as Figure 7 shown.
[0044] Example 2 (1) Powder treatment: 309S powder includes the following components calculated by mass percentage: Cr: 23%; Ni: 14%; Mn ≤ 2%; Si ≤ 1%; C ≤ 0.08%, and the rest is Fe element and other inevitable impurities; the particle size is 15-53μm.
[0045] The CoCrWCu powder includes the following components calculated by mass percentage: Cr: 28%; W: 4%; Cu: 4%; Mo≤1%; Fe≤3%; Si≤2%; Mn≤1%; C≤0.9%; the rest is Co element and other inevitable impurities; the particle size is 15-53μm.
[0046] The powder was dried in an oven before cladding.
[0047] (2) Substrate pretreatment: 7075 aluminum alloy is selected as the substrate material. Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale, and the surface of the aluminum alloy substrate obtained by the polishing treatment is cleaned with ethanol and acetone to at least remove grease. After cleaning, the aluminum alloy substrate is placed on a heating table and preheated to 300°C and kept heated continuously; (3) Preparation of transition layer: Argon gas was selected as the cladding protection gas and the cladding powder carrier gas. The 309S powder was clad on the surface of the aluminum alloy substrate by laser cladding technology to obtain the transition layer; the powder feeding gas flow rate was 15L / min, the laser power was 600W, the laser heat source moving speed was 20mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 0.9mm, and the distance between the laser head and the aluminum alloy substrate was 18mm; (4) Preparation of cladding layer Argon was selected as the cladding protection gas and the cladding powder carrier gas. The CoCrWCu powder was clad on the surface of the 309S transition layer by laser cladding technology to obtain a cladding layer (denoted as: CoCrW-4Cu), thereby preparing an antibacterial cobalt-based composite coating; the powder feeding gas flow rate was 15L / min, the laser power was 400W, the laser heat source moving speed was 10mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 1mm, and the distance between the laser head and the aluminum alloy substrate was 18mm.
[0048] (5) Antibacterial performance test: Test results: The antibacterial effect of the antibacterial cobalt-based composite coating is as follows Figure 5 , 6 As shown, the antibacterial rate is Figure 7 shown.
[0049] Example 3 (1) Powder treatment: 309S powder includes the following components calculated by mass percentage: Cr: 23%; Ni: 14%; Mn ≤ 2%; Si ≤ 1%; C ≤ 0.08%, and the rest is Fe element and other inevitable impurities; the particle size is 15-53μm.
[0050] The CoCrWCu powder includes the following components calculated by mass percentage: Cr: 28%; W: 4%; Cu: 8%; Mo≤1%; Fe≤3%; Si≤2%; Mn≤1%; C≤0.9%; the rest are Co element and other inevitable impurities; the particle size is 15-53μm.
[0051] The powder was dried in an oven before cladding.
[0052] (2) Substrate pretreatment: 7075 aluminum alloy is selected as the substrate material. Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale, and the surface of the aluminum alloy substrate obtained by the polishing treatment is cleaned with ethanol and acetone to at least remove grease. After cleaning, the aluminum alloy substrate is placed on a heating table and preheated to 300°C and kept heated continuously; (3) Preparation of transition layer: Argon gas was selected as the cladding protection gas and the cladding powder carrier gas. The 309S powder was clad on the surface of the aluminum alloy substrate by laser cladding technology to obtain the transition layer; the powder feeding gas flow rate was 15L / min, the laser power was 600W, the laser heat source moving speed was 20mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 0.9mm, and the distance between the laser head and the aluminum alloy substrate was 18mm; (4) Preparation of cladding layer Argon was selected as the cladding protection gas and the cladding powder carrier gas. The CoCrWCu powder was clad on the surface of the 309S transition layer by laser cladding technology to obtain a cladding layer (denoted as: CoCrW-8Cu), thereby preparing an antibacterial cobalt-based composite coating; the flow rate of the powder feeding gas was 15L / min, the laser power was 400W, the laser heat source moving speed was 10mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 1mm, and the distance between the laser head and the aluminum alloy substrate was 18mm.
[0053] (5) Antibacterial performance test, test results: The antibacterial effect of the antibacterial cobalt-based composite coating is as follows: Figure 5 , 6 As shown, the antibacterial rate is Figure 7 shown.
[0054] Comparative Example 1 (1) Powder processing: CoCrWCu powder includes the following components calculated by mass percentage: Cr: 28%; W: 4%; Cu: 2%; Mo≤1%; Fe≤3%; Si≤2%; Mn≤1%; C≤0.9%; the rest is Co element and other inevitable impurities; the particle size is 15-53μm.
[0055] The powder was dried in an oven before cladding.
[0056] (2) Substrate pretreatment: 7075 aluminum alloy is selected as the substrate material. Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale, and the surface of the aluminum alloy substrate obtained by the polishing treatment is cleaned with ethanol and acetone to at least remove grease. After cleaning, the aluminum alloy substrate is placed on a heating table and preheated to 300°C and kept heated continuously; (3) Preparation of antibacterial cobalt-based coating No transition layer is prepared, and argon is selected as the cladding protection gas and the cladding powder carrier gas. The CoCrW-2Cu powder is clad on the surface of the 7075 aluminum alloy by laser cladding technology to obtain an antibacterial cobalt-based coating; the flow rate of the powder feeding gas is 15L / min, the laser power is 600W, the laser heat source moving speed is 20mm / s, the powder feeding amount is 7g / min, the single-pass traverse is 0.9mm, and the distance between the laser head and the aluminum alloy substrate is 18mm; (4) Structural test: Test results are as follows Figure 8 Shown: The coating is detached from the substrate and cannot form an effective metallurgical bond.
[0057] Comparative Example 2 (1) CoCrWCu powder includes the following components calculated by mass percentage: Cr: 28%; W: 4%; Cu: 2%; Mo≤1%; Fe≤3%; Si≤2%; Mn≤1%; C≤0.9%; the rest is Co element and other inevitable impurities; the particle size is 15-53μm.
[0058] The powder was dried in an oven before cladding.
[0059] (2) Substrate pretreatment: 7075 aluminum alloy is selected as the substrate material. Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale, and the surface of the aluminum alloy substrate obtained by the polishing treatment is cleaned with ethanol and acetone to at least remove grease. After cleaning, the aluminum alloy substrate is placed on a heating table and preheated to 300°C and kept heated continuously; (3) Preparation of transition layer: Argon gas was selected as the cladding protection gas and the cladding powder carrier gas. The Fe60 powder was clad on the surface of the aluminum alloy substrate by laser cladding technology to obtain the transition layer; the powder feeding gas flow rate was 15L / min, the laser power was 600W, the laser heat source moving speed was 15mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 1mm, and the distance between the laser head and the aluminum alloy substrate was 18mm; (4) Structural test: Test results are as follows Fig. 9 As shown: the coating does not form an effective metallurgical bond with the substrate and the coating has many cracks.
[0060] Comparative Example 3 (1) Powder treatment: 309S powder includes the following components calculated by mass percentage: Cr: 23%; Ni: 14%; Mn ≤ 2%; Si ≤ 1%; C ≤ 0.08%, and the rest is Fe element and other inevitable impurities; the particle size is 15-53μm.
[0061] The CoCrWCu powder includes the following components calculated by mass percentage: Cr: 28%; W: 4%; Cu: 0%; Mo≤1%; Fe≤3%; Si≤2%; Mn≤1%; C≤0.9%; the rest are Co element and other inevitable impurities; the particle size is 15-53μm.
[0062] The powder was dried in an oven before cladding.
[0063] (2) Substrate pretreatment: 7075 aluminum alloy is selected as the substrate material. Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale, and the surface of the aluminum alloy substrate obtained by the polishing treatment is cleaned with ethanol and acetone to at least remove grease. After cleaning, the aluminum alloy substrate is placed on a heating table and preheated to 300°C and kept heated continuously; (3) Preparation of transition layer: Argon gas was selected as the cladding protection gas and the cladding powder carrier gas. The 309S powder was clad on the surface of the aluminum alloy substrate by laser cladding technology to obtain the transition layer; the powder feeding gas flow rate was 15L / min, the laser power was 600W, the laser heat source moving speed was 20mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 0.9mm, and the distance between the laser head and the aluminum alloy substrate was 18mm; (4) Preparation of antibacterial cobalt-based coating Argon was selected as the cladding protection gas and the cladding powder carrier gas. The CoCrW-0Cu powder was clad on the surface of the 309S transition layer by laser cladding technology to obtain an antibacterial cobalt-based coating; the flow rate of the powder feeding gas was 15L / min, the laser power was 400W, the laser heat source moving speed was 10mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 1mm, and the distance between the laser head and the aluminum alloy substrate was 18mm.
[0064] (5) Antibacterial performance test, test results: The antibacterial effect of CoCrW-0Cu coating is as follows Figure 5 , 6 As shown, the antibacterial rate is Figure 7 shown.
[0065] Comparative Example 4 (1) Powder treatment: 309S powder includes the following components calculated by mass percentage: Cr: 23%; Ni: 14%; Mn ≤ 2%; Si ≤ 1%; C ≤ 0.08%, and the rest is Fe element and other inevitable impurities; the particle size is 15-53μm.
[0066] The CoCrWCu powder includes the following components calculated by mass percentage: Cr: 28%; W: 4%; Cu: 1%; Mo≤1%; Fe≤3%; Si≤2%; Mn≤1%; C≤0.9%; the rest is Co element and other inevitable impurities; the particle size is 15-53μm.
[0067] The powder was dried in an oven before cladding.
[0068] (2) Substrate pretreatment: 7075 aluminum alloy is selected as the substrate material. Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale, and the surface of the aluminum alloy substrate obtained by the polishing treatment is cleaned with ethanol and acetone to at least remove grease. After cleaning, the aluminum alloy substrate is placed on a heating table and preheated to 300°C and kept heated continuously; (3) Preparation of transition layer: Argon gas was selected as the cladding protection gas and the cladding powder carrier gas. The 309S powder was clad on the surface of the aluminum alloy substrate by laser cladding technology to obtain the transition layer; the powder feeding gas flow rate was 15L / min, the laser power was 600W, the laser heat source moving speed was 20mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 0.9mm, and the distance between the laser head and the aluminum alloy substrate was 18mm; (4) Preparation of cladding layer Argon was selected as the cladding protection gas and the cladding powder carrier gas. The CoCrW-1Cu powder was clad on the surface of the 309S transition layer by laser cladding technology to obtain a cladding layer (denoted as: CoCrW-1Cu), thereby preparing an antibacterial cobalt-based composite coating; the flow rate of the powder feeding gas was 15L / min, the laser power was 400W, the laser heat source moving speed was 10mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 1mm, and the distance between the laser head and the aluminum alloy substrate was 18mm.
[0069] (5) Antibacterial performance test: Test results: The antibacterial effect of CoCrW-1Cu coating is as follows Figure 5 , 6 As shown, the antibacterial rate is Figure 7 shown.
[0070] Comparative Example 5 (1) Powder treatment: 309S powder includes the following components calculated by mass percentage: Cr: 23%; Ni: 14%; Mn ≤ 2%; Si ≤ 1%; C ≤ 0.08%, and the rest is Fe element and other inevitable impurities; the particle size is 15-53μm.
[0071] The CoCrWCu powder includes the following components calculated by mass percentage: Cr: 28%; W: 4%; Cu: 2%; Mo≤1%; Fe≤3%; Si≤2%; Mn≤1%; C≤0.9%; the rest are Co element and other inevitable impurities; the particle size is 15-53μm.
[0072] The powder was dried in an oven before cladding.
[0073] (2) Substrate pretreatment: 7075 aluminum alloy is selected as the substrate material. Before the cladding treatment, the aluminum alloy substrate is first polished to remove the oxide scale, and the surface of the aluminum alloy substrate obtained by the polishing treatment is cleaned with ethanol and acetone to at least remove grease. After cleaning, the aluminum alloy substrate is placed on a heating table and preheated to 300°C and kept heated continuously; (3) Preparation of transition layer: Argon gas was selected as the cladding protection gas and the cladding powder carrier gas. The 309S powder was clad on the surface of the aluminum alloy substrate by laser cladding technology to obtain the transition layer; the powder feeding gas flow rate was 15L / min, the laser power was 600W, the laser heat source moving speed was 20mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 0.9mm, and the distance between the laser head and the aluminum alloy substrate was 18mm; (4) Preparation of cladding layer Argon was selected as the cladding protection gas and the cladding powder carrier gas. The CoCrWCu powder was clad on the surface of the 309S transition layer by laser cladding technology to obtain a cladding layer, thereby preparing a composite coating; the flow rate of the powder feeding gas was 15L / min, the laser power was 700W, the laser heat source moving speed was 15mm / s, the powder feeding amount was 7g / min, the single-pass traverse was 1mm, and the distance between the laser head and the aluminum alloy substrate was 18mm.
[0074] (5) Structural test: Test results: Fig.10 Shown: Cracks and pores appear in the coating.
[0075] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0076] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. An antibacterial cobalt-based composite coating for aluminum alloy surface, characterized in that: include: A 309S metallurgical bonding transition layer and a CoCrWCu cladding layer are sequentially formed on the surface of an aluminum alloy substrate; wherein the 309S metallurgical bonding transition layer comprises the following elemental components: C, Ni, Mn, Si, C and Fe; the CoCrWCu cladding layer comprises the following elemental components: Cr, W, Cu, Mo, Fe, Si, Mn, C and Co; the Cu content in the CoCrWCu cladding layer is 2-4wt%; the antibacterial cobalt-based composite coating is prepared by laser cladding technology.
2. The antibacterial cobalt-based composite coating according to claim 1, characterized in that: The 309S metallurgical bonding transition layer includes the following element components calculated by mass percentage: Cr 22-24%, Ni 12-15%, Mn ≤2%, Si ≤1%, C ≤0.08%, and the rest includes Fe and unavoidable impurities; And / or, the CoCrWCu cladding layer includes the following element components calculated by mass percentage: Cr 26-32%, W 3-6%, Cu 2-4%, Mo ≤1%, Fe ≤3%, Si ≤2%, Mn ≤1%, C ≤0.9-1.4%, and the rest includes Co element and unavoidable impurities.
3. The antibacterial cobalt-based composite coating according to claim 1, characterized in that: The thickness of the 309S metallurgical bonding transition layer is 500-1000 μm; and / or, the structure of the 309S metallurgical bonding transition layer is a single austenite phase; And / or, the thickness of the CoCrWCu cladding layer is 700-1500 μm; And / or, the structure of the CoCrWCu cladding layer is a single austenite phase.
4. The method for preparing an antibacterial cobalt-based composite coating for an aluminum alloy surface as claimed in any one of claims 1 to 3, characterized in that: include: Providing an aluminum alloy substrate; Laser cladding technology is used to clad 309S powder material on the surface of the aluminum alloy substrate to form a 309S metallurgical bonding transition layer; Furthermore, a high-speed laser cladding technology is used to clad the CoCrWCu powder material on the surface of the 309S metallurgical bonding transition layer, thereby preparing an antibacterial cobalt-based composite coating for the surface of the aluminum alloy.
5. The preparation method according to claim 4, characterized in that: The 309S powder material includes the following element components calculated by mass percentage: Cr 22-24%, Ni 12-15%, Mn ≤2%, Si ≤1%, C ≤0.08%, and the rest includes Fe and unavoidable impurities; And / or, the CoCrWCu powder material comprises the following element components calculated by mass percentage: Cr 26-32%, W 3-6%, Cu 2-4%, Mo ≤1%, Fe ≤3%, Si ≤2%, Mn ≤1%, C ≤0.9-1.4%, and the rest comprises Co element and unavoidable impurities; And / or, the 309S powder material is spherical powder with a particle size of 15-53 μm; And / or, the CoCrWCu powder material is in the form of spherical powder with a particle size of 15-53 μm.
6. The preparation method according to claim 4, characterized in that: Specifically include: The laser cladding technology is used to clad the 309S powder material on the surface of the aluminum alloy substrate to obtain a 309S metallurgical bonding transition layer; wherein the flow rate of the powder feeding gas used in the laser cladding technology is 12~20L / min, the laser power is 500~800W, the moving speed of the laser heat source is 18~22mm / s, the powder feeding amount is 6~8g / min, the single-channel lateral movement is 0.8~1.0mm, the distance between the laser head and the aluminum alloy substrate is 17~19mm, and the powder feeding gas includes argon and / or helium.
7. The preparation method according to claim 4, characterized in that: Specifically include: The CoCrWCu powder material is clad on the surface of the 309S metallurgical bonding transition layer by laser cladding technology to obtain a CoCrWCu cladding layer; wherein the flow rate of the powder feeding gas used in the laser cladding technology is 14-16 L / min, the laser power is 400-600 W, the moving speed of the laser heat source is 8-12 mm / s, the powder feeding amount is 6-8 g / min, the single-pass lateral displacement is 0.9-1.2 mm, and the distance between the laser head and the 309S metallurgical bonding transition layer is 17-19 mm; the powder feeding gas includes argon and / or helium.
8. The preparation method according to claim 4, characterized in that: Also includes: The aluminum alloy substrate is first polished to remove the oxide scale, and then cleaned; wherein the cleaning process includes: using ethanol or acetone to clean the surface of the aluminum alloy substrate obtained by the polishing process, at least to remove grease; and, placing the cleaned aluminum alloy substrate on a heating table and preheating it to 250-350° C. and maintaining continuous heating; And / or, the preparation method further comprises: firstly drying the 309S powder material and the CoCrWCu powder material.
9. The preparation method according to claim 4, characterized in that: The aluminum alloy substrate comprises an aluminum alloy plate, and the thickness of the aluminum alloy plate is above 10 mm.
10. Use of the antibacterial cobalt-based composite coating for aluminum alloy surface according to any one of claims 1 to 3 in the field of marine equipment protection.